2020
DOI: 10.1088/1361-665x/abb645
|View full text |Cite
|
Sign up to set email alerts
|

Development and damping properties of a seismic linear motion damper with MR fluid porous composite rotary brake

Abstract: The particle sedimentation of the dispersed particles in magnetorheological (MR) fluids when off-working has been a challenging problem, causing adverse effect to their practical applications. In order to solve this problem, ‘MR fluid porous composite’ made of porous materials impregnated with MR fluid has been fabricated in this work. Its effect to prevent the particle sedimentation has been proved through contrast experiment. Its MR effect has also been measured and verified using a hand-made oscillatory rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The internal porous network can effectively protect the magnetic particle chains (Nakano, 2011). Experimental results showed that the mechanical performance was improved by MRF-PF (Nakano et al, 2020). What’s more, MRF-PF was used in a variable inertial flywheel as the working medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal porous network can effectively protect the magnetic particle chains (Nakano, 2011). Experimental results showed that the mechanical performance was improved by MRF-PF (Nakano et al, 2020). What’s more, MRF-PF was used in a variable inertial flywheel as the working medium.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these advantages, MRF-PF can be used into vehicle, sensor, and other semi-active control applications. According to the relative works, most research works are focus on the engineering applications to improve the output performance (Dong et al, 2018; Nakano, 2011; Nakano et al, 2020). Preparation and rheological properties of MRF-PF are not tested and further analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, particle chains can be supported by internal networks to reinforce the output performance [28]. Experimental results show that MRF porous fabric composite (MRF-PF) has no sedimentation after 30 d. The maximum force of MR damper with MRF-PF reaches to 20 kN under the current of 0.5 A [29]. MRF-PF with non-woven fabric had been used in flywheel to adjust the rotational inertia with a range of 27.2% [30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigations of MRF-PF are mainly focus on the improvement of output damping force in engineering applications. MRF-PF is mostly regarded as a carrier to hold MRF in working regions [29,30]. Constitute model of MRF-PF are always ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Its rheological properties are often described by Bingham, Herschel-Bulkley, and Casson-Plastic models [4,5]. Based on the working mode of MRFs, the MR actuator can be divided into linear [6] and rotary MR actuators [7]. Linear MR actuators have been successfully applied in automobile suspension systems as dampers.…”
Section: Introductionmentioning
confidence: 99%